Academic Debate as a Didactic Strategy for the Training of Argumentative Skills and the Approach to Scientific Dialogue - Carrillo García, Stefany; Nevado Castellanos, Karen (Rastros Rostros, 2017)
Introduction: This article derives from the research carried out in the classroom with a group of students who were in the first level of the undergraduate program Chemical Engineering at the Universidad Industrial de Santander in 2015. It aims to analyze the academic debate as a didactic alternative that allows to develop oral argumentative discursive strategies in students. Also, the promotion of scientific dialogue is studiedas a social opportunity to reinforce critical and reflexive skills. Methodology: The action research conducted is oriented by a qualitative methodological approach fordata application and analysis, taking as reference James McKernan’s postulates and Perelman and Olbrecht-Tyteca’ model theory of argumentation. Results: In this regard, from the diagnosis of an academic need, a didactic intervention plan in the classroomwas designed for said university students, who participated in debates on topics related to their disciplinary field. Conclusions: The results show that a comprehensive training strategy is necessary for the development of epistemic operations and academic culture that require argumentative skills. In addition, specific learning, through genres, builds significant skills, but it must be an ongoing process that deserves more than one academic semester.
Keywords: argumentation; academic culture; debate; discourse